Boosting the Quality Factor of the Shadow Bandpass Filter - Seangrawee Buakaew; Chariya Wongtaychatham (Journal of Circuits Systems and Computers, 2022)
This paper proposes a new method to increase the quality factor of the shadow bandpass filter. The proposed circuit topology is simple, with the use of conventional biquad cell along with external amplifiers. The major advantageous feature is that the quality factor of the filter is boosted up whereas the gain of the external amplifier is significantly reduced. Moreover, the presented idea can be applied to the shadow filter in both current and voltage modes. The proposed scheme is justified via circuit performance. The performance is compared with the previous research works in the same arena. The results show that a feedback signal and a properly chosen gain incredibly boost up the quality factor of the shadow bandpass filter. Simulations by PSpice using 0.18-[Formula: see text]m CMOS-level parameters confirm the validity of the proposed work.
Keywords: Analog and Mixed-Signal Circuit Design; Radio Frequency Integrated Circuit Design; Electrostatic Discharge in Electronics